2012
DOI: 10.14310/horm.2002.1364
|View full text |Cite
|
Sign up to set email alerts
|

High TSH and low T4 as prognostic markers in older patients

Abstract: th percentile), and mortality assessed during an 18-month follow-up period after their hospital discharge. rESulTS: Out of 2599 older patients admitted to our hospital, 7% had TFT performed for various reasons. The patients who had TFT were mostly women and presented in a more serious clinical condition compared to the rest of the patients. The patients were grouped as per their thyroid values as follows: 61% of them had a non-thyroidal illness, 25% were euthyroid, 7% had overt hyperthyroidism, 5% overt hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
12
0
3
Order By: Relevance
“…This clinical presentation in hospitalized elderly patients is associated with increased morbidity and mortality rates. The endocrine emergencies exhibit higher morbidity and mortality rates in elderly patients who undergo thyroid surgical procedures (5-8). …”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…This clinical presentation in hospitalized elderly patients is associated with increased morbidity and mortality rates. The endocrine emergencies exhibit higher morbidity and mortality rates in elderly patients who undergo thyroid surgical procedures (5-8). …”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Thus, reliance on thyroid function tests in hospitalized patients is questionable and treatment decisions are infrequently based on laboratory values performed in hospitalized patients. This is particularly problematic in elderly individuals where normal thyroid function is ill-defined and where the influence of NTIS may be more significant [4][5][6][7]. A metaanalysis and systematic review reported that TSH ▼ It is unclear whether TSH should be obtained in elderly hospitalized patients as several factors associated with hospitalization influence these levels, which may not truly represent the thyroid status of the individual.…”
mentioning
confidence: 99%
“…Nuestros resultados confirman que la prevalencia de alteraciones en la función tiroidea en ancianos hospitalizados por enfermedad aguda es notablemente alta, alrededor de las tres cuartas partes de los pacientes, principalmente a expensas de SEE, como se ha expuesto anteriormente (39,125,128).…”
Section: Vivosunclassified
“…El síndrome de T3 baja es la alteración más frecuente en las pruebas de función tiroidea encontrada en ancianos hospitalizados por enfermedad aguda, y se detecta entre un 60-66% de los pacientes según los estudios (39,125,128). Sin embargo, hay que considerar que en ocasiones esta alteración es transitoria, normalizándose los niveles séricos de T3 L en aproximadamente un 30% al mes del alta hospitalaria (133).…”
Section: Vivosunclassified
See 1 more Smart Citation